Potential protective effect of bacterial prodigiosin on the pancreas in diabetic rats: alleviating inflammation, oxidative stress, and histological damage with antidiabetic properties - Walaa I. El-Sofany; Ahlam F. Alshammari; Mona Zaheed Alshammari; Hissah Khashman Alshammari; Nawal S. Alshammari; Khaled Hamden (Journal of Agriculture and Food Research)
The goal of this study was to examine, for the first time, the effects of prodigiosin (PG) administration on key inflammation enzymes, lymphocyte infiltration, oxidative status, as well as hepatic and renal function in diabetic rats. The results showed that PG, at a dose of 150 mg/kg body weight via gastric gavage, significantly reduced lymphocyte infiltration and pancreatic MPO activity by 63 %. Additionally, PG suppressed key enzymes related to pancreas inflammation, including PLA2, PGS, and ELA, by 75, 78, and 56 %, respectively. PG also demonstrated strong antioxidant activity, reducing H2O2, TBARS, and TOS, while enhancing TAS by 68 %. These anti-inflammatory and antioxidant effects were further confirmed by an increase in the number of islets of Langerhans in the pancreas and β-cells per islet, as well as the β-cells/total cells ratio, leading to an increase in insulin production. Moreover, PG administration at dose 150 mg/kg bw reduced blood glucose and HbA1c levels by 54 and 31 %, respectively, compared to untreated diabetic rats. This study also thoroughly investigated that PG intake in diabetic rats protects hepatic and renal function, as evidenced by biochemical analyses such as AST, ALT, and LDH activities, as well as Cr, ALB, and Urea levels. Additionally, histological studies showed that this compound significantly reduces inflammation and lymphocytic infiltration. Therefore, PG demonstrates potent anti-inflammatory, antioxidant, and anti-diabetic properties, making it a promising candidate for both pharmaceutical and food applications. Additionally, clinical study is important to validate these results as well as their potential application in food.